Efficient and Secure Resource Management in Home M2M Networks - Yue Lai; Jiawen Kang; Rong Yu (International Journal of Distributed Sensor Networks, 2013)
In recent years, M2M networking is an active research topic in both academic and industrial fields. Home M2M networks, as an important branch of M2M networks, have attracted wide concerns for home application. In this paper, we first present a brief overview of home M2M networks. Then we introduce a hierarchical architecture of home M2M networks and describe the approach of devices management and services discovery. After that, we focus on the security authentication with centralized node and an improved method of available bandwidth measurement. With the centralized node, our system is more efficient and secure, because of efficient resource management and users' anonymity protection. Compared to existing bandwidth measurement methods, our method takes up less additional bandwidth, saves more time, and has a higher accuracy for measurement. Experiments are carried out to demonstrate the effectiveness and accuracy of the proposed scheme.